Fatigue performance of additive manufactured TiAl6V4 using electron and laser beam melting. (January 2017) - Greitemeier, Daniel; Palm, Frank; Syassen, Freerk; Melz, Tobias
Abstract: Increasingly, additive manufacturing is considered to reduce weight and lead time of aerospace components. Despite the high potential of this manufacturing technology, reliable mechanical properties are an essential prerequisite for future series production. Therefore, the aim of this work was to contribute to an improved understanding of the factors influencing the mechanical properties of laser powder bed and electron beam melted TiAl6V4. Therefore, tensile tests, fracture toughness tests, fatigue crack growth measurements for different r -ratios as well as high cycle fatigue properties were determined for different surface roughness and heat treatments.